Detection of Specific IgG-Antibodies Against Toxoplasma gondii in the Serum and Milk of Domestic Donkeys During Lactation in China: A Potential Public Health Concern - Chen, Long; Zhao, Zi-Jian; Meng, Qing-Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is a worldwide zoonotic protozoan. Donkeys may be susceptible to many pathological agents and may act as carriers of pathogens for other animal species and humans. However, data on T. gondii infection in donkey during lactation and on the contamination status of T. gondii in donkey milk are lacking. A cross-sectional study was conducted to evaluate the variation of anti-T. gondii antibodies in blood and milk of domestic donkeys during the lactation. From January 2019 to March 2020, a total of 418 domestic donkeys were randomly selected from Shandong province, eastern China. Anti-T. gondii antibodies were found in 11.72 % (49/418) serum and 9.81% (41/418) milk samples by a commercial ELISA kit, respectively. The consistency between serum and milk results are very high (Spearman's coefficient=0.858, p-value<0.0001 and Kendall's tau=0.688, p-value<0.0001), particularly at the 41-50 day of lactation. The present results of statistical analysis showed that none of selected variables were significantly associated with T. gondii infection in domestic donkeys. This is the first report of donkey’s milk contaminated with T. gondii in China. These results suggest that it is a potential risk factor for human to get infection through the consumption of raw milk from naturally infected donkeys.